Gene polymorphisms and febrile neutropenia in acute leukemia-no association with IL-4, CCR-5, IL-1RA, but the MBL-2, ACE, and TLR-4 are associated with the disease in Turkish patients: A preliminary study - Pehlivan, Mustafa; Haydaroğlu Şahin, Handan; Özdilli, Kürşat; Onay, Hüseyin; Özcan, Ali; Özkinay, Ferda; Pehlivan, Sacide (Mary Ann Liebert, Inc., 2014)
Aims: The aim of this study was to investigate the mannose-binding lectin 2 (MBL-2), interleukin (IL)-4, Toll-like receptor 4 (TLR-4), angiotensin converting enzyme (ACE), chemokine receptor 5 (CCR-5), and IL-1 receptor antagonist (RA) gene polymorphisms (GPs) in acute leukemias (ALs) and to evaluate their roles in febrile neutropenia (FN) resulting from chemotherapy. Methods: The study included 60 AL patients hospitalized between the period of July 2001 and August 2006. Polymorphisms for the genes ACE(I/D), CCR-5, IL-1RA, MBL-2, TLR-4, and IL-4 were typed by polymerase chain reaction (PCR) and/or PCR-restriction fragment length polymerase. Genotype frequencies for these genes were compared in the patient and control groups. The relationships between the genotypes and the body distribution of infections, pathogens, the duration of neutropenia, and febrile episodes in AL patients were evaluated. Results: No significant differences in either the genotype distribution or the allelic frequencies of TLR-4, IL-4, CCR-5, IL-1RN GPs were observed between patients and healthy controls. The AB/BB genotype (53.3%) in the MBL-2 gene was found to be significantly higher in the AL patients compared with control groups. There were correlations between the presence of MBL-2, TLR-4, and ACE polymorphisms and clinical parameters due to FN. Overall, bacteremia was more common in MBL BB and ACE DD. Gram-positive bacteremia was more common in ACE for ID versus DD genotype. Gram-negative bacteremia was more common for both the MBL-2 AB/BB genotype and TLR-4 AG genotype. Median durations of febrile episodes were significantly shorter in ACE DD and MBL AB/BB. Conclusion: Although TLR-4, ACE, and MBL-2 GPs have been extensively investigated in different clinical pictures, this is the first study to evaluate the role of these polymorphisms in the genetic etiopathogenesis of FN in patients with ALs. As a conclusion, TLR-4, ACE, and MBL-2 genes might play roles in the genetic etiopathogenesis of FN in patients with ALs.
WOS: 000339392600005
PubMed ID: 24819208
Keywords: Polymorphisms; Mannose-Binding Lectin 2 (MBL-2); Interleukin (IL)-4; Toll-Like Receptor 4 (TLR-4); Angiotensin Converting Enzyme (ACE); Chemokine Receptor 5 (CCR-5); IL-1 Receptor Antagonist (RA)